2017
DOI: 10.3390/jmse5010009
|View full text |Cite
|
Sign up to set email alerts
|

Energy Balance of Biogas Production from Microalgae: Effect of Harvesting Method, Multiple Raceways, Scale of Plant and Combined Heat and Power Generation

Abstract: Abstract:A previously-developed mechanistic energy balance model for production of biogas from the anaerobic digestion of microalgal biomass grown in open raceway systems was used to consider the energetic viability of a number of scenarios, and to explore some of the most critical parameters affecting net energy production. The output demonstrated that no single harvesting method of those considered (centrifugation, settlement or flocculation) produced an energy output sufficiently greater than operational en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
0
17
0
2
Order By: Relevance
“…One of the key factors in achieving a positive energy balance in algal AD is a high conversion of organic material to methane; increasing CH 4 yield from AD of seaweed was found to be a vital factor in improving process energy balance and reducing greenhouse gas emissions [41,53,112]. Real-world yields of biogas from digestion of many algae are substantially below the theoretical maximum.…”
Section: Challenges To Biogas Production From Macro-and Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…One of the key factors in achieving a positive energy balance in algal AD is a high conversion of organic material to methane; increasing CH 4 yield from AD of seaweed was found to be a vital factor in improving process energy balance and reducing greenhouse gas emissions [41,53,112]. Real-world yields of biogas from digestion of many algae are substantially below the theoretical maximum.…”
Section: Challenges To Biogas Production From Macro-and Microalgaementioning
confidence: 99%
“…Ter Veld [52] found an EORI > 3 for biogas produced from microalgal biomass grown in high rate algal ponds (HRAPs) and concluded that microalgae-based biofuel sustainability was not set by areal productivity or lipid content in the algae but by the recovery of nutrients. Another energy balance model for the production of biogas from microalgae grown on wastewater found energy returns on operational energy invested greater than 3 with the use of nutrients from wastewater being a crucial component in producing a positive net energy balance [53,54]. It is also critical to minimise fresh water use in microalgal biofuel production not merely to minimise cost but also to circumvent a future problem with 'water versus fuel'.…”
Section: Introductionmentioning
confidence: 99%
“…A 1/3 higher biogas yield and a 1/2 lower labor cost did not change the economic status of both processes, due to the high cost of fertilizer and building photobioreactors for microalgae cultivation. Milledge and Heaven [74,129] performed an energy balance of biogas production from microalgae. Their research emphasized a combination of dewatering methods, as well as the efficient exploitation of the heat generated by the combustion of biogas in combined heat and power (CHP) units to show the energetic viability of the whole process.…”
Section: State Of the Art: Tea Of Microalgal Biogasmentioning
confidence: 99%
“…The volume of water contaminated by cyanobacteria as well as the numbers of cyanobacteria themselves in water bod ies of Ukraine is enormous. Thus, according to the data of re search on water of the Kremenchutske Reservoir only with the area of the water table of 2250 km 2 with the volume of shallow waters of 828 million m 3 , with the average density of saturation of water with cyanobacteria of 50 kg/m 3 , their overall biomass makes 4.14 ⋅ 10 7 tonnes of accumulation throughout the sum mer vegetative season [2].…”
Section: Developing a Technology For Treating Blue-green Algae Biomasmentioning
confidence: 99%
“…At the same time, domestic and foreign researchers have presented solid evidence of the fact that under certain conditions of processing bluegreen algae (cyanobacteria), useful raw mate rial for producing biogas as heatpower engineering fuel can be obtained. Thus, [3] studies a method for producing biogas as a result of anaerobic methane digestion of water solution substrate of a fermentation medium and bluegreen algae suspension. The attained results accord well with findings described in [4].…”
Section: Developing a Technology For Treating Blue-green Algae Biomasmentioning
confidence: 99%